Pedagogical Fundamentals Of Developing Intellectual And Creative Skills Of The Students - Ortikova Ozoda Sharofovna; Utaboyev Baxtiyor Safarovich (Genius Journals, 2022)
This article expresses feedback related to the development of intellectual and creative abilities of pupil-youth and considers the pedagogical bases
Keywords: Intelligence; Coefficient; Ability; Creative